Long-term effect of FYM and inorganic fertilizers on soil quality and sustainable productivity of soybean (Glycine max) and safflower (Carthamus tinctorius) in Vertisol - MESHRAM, N A; ISMAIL, SYED; PINJARI, S S (The Indian Journal of Agricultural Sciences, 2018)
A long-term experimental study was conducted at the research farm under All India Coordinated Research Project, Vasantrao Naik Marathwada Krishi Vidyapeeth Parbhani, Maharashtra to assess the impact of continuous cultivation of soybean [Glycine max (L.) Merr.] and safflower (Carthamus tinctorius L.) in Vertisol (Typic Haplusterts) using varying levels of chemical fertilizer and manure applications on approximately 7th cycle data on soil quality indicators (physical, chemical and biological), a sustainable yield index (SYI) and a soil quality index (SQI). Application of NPK fertilizers in combination with FYM also significantly increased in benefit cost ratio, higher average grain yield of soybean and safflower and enhanced the soil quality and sustainability of the system compared to the control and plots in receipt of fertilizers. A greater SYI and SQI in the 100% NPK+FYM@ 5 Mg/ha treatment demonstrated the importance of using a chemical fertilizer in combination with FYM. Among the different nutrient management supply system, economical and more sustainable nutrient management system (NPK+FYM) could be used to monitor soil quality and getting higher productivity of soybean and safflower in a semiarid agro-ecosystem.